Oral iron supplementation effects on maternal and infant iron status and on breast milk iron concentration (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2010)
The effects of oral iron supplementation on maternal and infant iron status and on breast milk iron concentration were assessed among 32 lactating women and their exclusively breastfed infants. Lactating women were supplemented with oral iron supplements for three to six months depending on their iron status. Anemic infants were supplemented with oral iron drops daily for three months. Maternal and infant iron status and breast milk iron concentration were determined at three time points. At baseline, 31% of lactating mothers were anemic and 44% had depleted iron stores (serum ferritin <15mg/ml). After 3 months of iron supplementation, hemoglobin concentration increased among lactating mothers, with a significant increase among the anemic mothers. At 6 months, all the lactating women had normal hemoglobin levels but 20% still had depleted iron stores, implying the need for a longer period of supplementation. The mean breast milk iron of mothers at baseline was 0.04±0.02 mg/100 ml, which remained until 3 months but generally declined to 0.03±0.01 mg/100 ml at 6 months. The concentration, however, remained among anemic mothers who continued taking iron supplements until 6 months. Among infants, mean hemoglobin (179±26 g/L) which was generally high at birth decreased significantly (119±13 g/L) at 3 months of age and 12% were found to be anemic. At 6 months, hemoglobin increased significantly among the iron-supplemented anemic infants. In conclusion, moderate iron deficiency anemia exists among lactating mothers and their exclusively breastfed infants during the first 6 months of lactation. Oral iron supplementation significantly improved iron status of lactating women and infants. Breast milk iron declined through the course of lactation but tend to be constant among iron-supplemented anemic women.